International Dialogue on Migration No. 29 - International Organization for Migration (United Nations, 2019)
Against this background, the 2019 International Dialogue for Migration (IDM) – IOM’s flagship initiative for policy discussion – was dedicated to deliberating how to engage and empower young people as key partners in migration governance. The 2019 IDM responded to calls for greater engagement with young people from participants at previous IDMs and was aligned with the United Nations Youth Strategy, which recognizes the potential of young people to advance progress in many policy areas, thanks to their first-hand experience. This publication aims to provide an analysis of the role of young people in migration governance, how to engage them and how to unlock their potential to respond to the challenges and opportunities presented by migration. Moreover, it offers the reader an exhaustive collection of best practices, lessons learned and recommendations gathered from the discussions.